A Two-Step Strategy for Fabrication of Biocompatible 3D Magnetically Responsive Photonic Crystals - Liu, Hui; Wang, Caiqin; Wang, Peixi; Liu, Nan; Du, Qingfeng (Frontiers in Chemistry, 2019)
Extremely stable and biocompatible 3D magnetically responsive photonic crystals (MRPCs) are successfully prepared in aqueous solution. Classic hydrothermal synthesis was applied for preparation of the Fe3O4@C core. Modified Stöber method was then employed for synthesis of the different size of Fe3O4@C@SiO2. Unlike the traditional magnetic nanoparticles, the highly negative charged superparamagnetic nanospheres (SMNs), i.e., the double-shell structure Fe3O4@C@SiO2 are capable of rapidly self-assembling into 3D MRPCs with full visible and various colors that can be periodically and reversibly tuned under different kinds of external magnetic fields (EMFs) within 1 s. The assembling behavior and mechanism of the 3D MRPCs under EMF were monitored and analyzed. The preparation is simple and the size of the SMN is easily controllable by adjusting the amount of catalyst. Compared with the previous works, the synthesized 3D MRPCs are hydrophilic, and exhibit extremely high stability after 6-month storage. To conclude, our study provides an effective two-step strategy for fabrication of biocompatible 3D MRPCs and it reveals great potentials in biological fields.